Gestión contable y su efecto en la operatividad de la empresa de servicio de entregas a domicilio en el Cantón Quevedo período 2021-2022 - Arteaga Mayorga, Clara Beatriz (2024)
The investigation was carried out in the home delivery service company “Quevexpress San Carlos”, located in the Quevedo Canton, San Carlos Parish. Its purpose was to evaluate Accounting Management and its effect on the operation of the home delivery service company Quevexpress San Carlos for the 2021-2022 period. Descriptive and field methods were used with inductive and deductive approaches in the research and collection of primary and direct information. As a study technique, an interview was carried out with the person in charge of the accounting area and a survey of the operational staff, which allowed the general diagnosis of the accounting situation and the operation of the company, where the result was that the person in charge of accounting management did not has adequate knowledge in the area and the company does not have technological tools that facilitate recording, communicating, classifying and reporting the accounting management carried out and lack of planning in the determined functions. According to the analysis and comparison carried out on income, the company reflects a decrease of 10% in the 2021-2022 period. The survey results provide a detailed view of areas for improvement at the Quevexpress San Carlos Company in relation to operations management and operational effectiveness. These findings can serve as a basis for future improvement actions that allow the company to achieve a higher level of efficiency and customer satisfaction.